Simulation studies on simultaneous power, cooling and purified water production using vapour absorption refrigeration system. (5th March 2018) - Praveen Kumar, G.; Saravanan, R.; Coronas, Alberto
Highlights: A novel absorption system based combined cooling, power, desalination is proposed. The system can able to provide simultaneous power, cooling and purified water. Energetic and exergetic performance of combined cycles is analysed. Highest energy and exergy efficiencies are obtained at 95 °C heat source temperature.